The Bundesbank's Communications Strategy and Policy Conflicts with the Federal Government - Pierre L. Siklos; Martin T. Bohl (European University Viadrina, The Postgraduate Research Programme: Capital Markets and Finance in the Enlarged Europe, 2005)
In this paper we provide an estimate of the likelihood of conflict between the federal government and the Bundesbank for the 1989 – 1998 period. We rely on a novel proxy for the impact of public communication by Bundesbank officials on the probability of conflict, in addition to interest rate, exchange rate, money supply behavior, as well as electoral influences. The empirical evidence is consistent with the view that speeches by the Bundesbank President dealing with inflation and economic policy are a positive source of conflict in a probabilistic sense. Conflict was not a constant but flared up at times of economic stress and could be exacerbated by the "talking" of Bundesbank officials.
Keywords: E63; E32; E58; 330; Deutsche Bundesbank; Conflict; Central Bank Communication; Political Factors